Does using the sociodental approach in oral health care influence use of dental services and oral health of adolescents living in deprived communities? a one-year follow up study - Andressa Coelho Gomes; Mario Vianna Vettore; Larissa Neves Quadros; Maria Augusta Bessa Rebelo; Janete Maria Rebelo Vieira (BMC, 2023)
Abstract Background Oral health needs assessment is important for oral health care planning. This study compared dental treatment needs between normative and sociodental needs. We also longitudinally examined the relationships of baseline sociodental needs measures and socioeconomic status with one-year follow up measures of use of dental services, dental caries, filled teeth, and oral health-related quality of life (OHRQoL). Methods A prospective study was conducted with 12-year-old adolescents from public schools in deprived communities in the city of Manaus, Brazil. Validated questionnaires were used to collect adolescents' sex and socioeconomic status, OHRQoL (CPQ11 − 14) and behaviours (sugar intake, frequency of toothbrushing, regular use of fluoridated toothpaste and pattern of dental attendance). Normative need was assessed according to decayed teeth, clinical consequences of untreated dental caries, malocclusion, dental trauma, and dental calculus. The relationships between variables were tested thorough Structural equation modelling. Results Overall 95.5% of adolescents had normative dental treatment needs. Of these, 9.4% were classified as high level of propensity. Higher normative/impact need and greater propensity-related need directly predicted use of dental services at one-year follow up. The latter mediated the association of normative/impact need and propensity-related need with incidence of dental caries and filled teeth. Normative/impact need and use of dental services were directly associated with filled teeth at one-year follow up. Poor OHRQoL at one-year follow-up was directly predicted by higher normative/impact need at baseline and less filled teeth at one-year follow up. Greater socioeconomic status was directly associated with better propensity-related need. Socioeconomic status indirectly predicted incidence of dental caries and filled teeth via propensity-related need and use of dental services. Conclusions Sociodental needs measures were related to use of dental services, dental caries, filled teeth and OHRQoL after one year among adolescents living in deprived communities. Adolescents with dental needs treatment priorities according to the sociodental approach had more filled teeth via use of dental services. Dental services utilisation did not attenuate the impact of normative and impact-related need on dental caries incidence and poor OHRQoL after one year. Our findings suggest the importance of developing oral health promotion and enhancing access to dental care to improve oral health of adolescents living in deprived communities.